2016
DOI: 10.1007/s10862-016-9556-8
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Prenatal Maternal Stress and Autonomic Arousal in Predicting Conduct Problems and Psychopathic Traits in Children

Abstract: Background Evidence has suggested that neurobiological deficits combine with psychosocial risk factors to impact on the development of antisocial behavior. The current study concentrated on the interplay of prenatal maternal stress and autonomic arousal in predicting antisocial behavior and psychopathic traits. Methods Prenatal maternal stress was assessed by caregiver’s retrospective report, and resting heart rate and respiratory sinus arrhythmia (RSA) were measured in 295 8- to 10-year-old children. Child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 56 publications
(65 reference statements)
1
47
2
Order By: Relevance
“…Symptom non-specificity has long been an issue in defining PTSD, as many PTSD symptoms overlap with other mental health disorders, including mood and anxiety disorders (Spitzer et al, 2007), although this is a problem inherent to many DSM diagnoses, not just PTSD (Byllesby et al, 2016; Watson, 2005; Zbozinek et al, 2012). Our findings indicate that some of these non-specific symptoms are important to the PTSD network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptom non-specificity has long been an issue in defining PTSD, as many PTSD symptoms overlap with other mental health disorders, including mood and anxiety disorders (Spitzer et al, 2007), although this is a problem inherent to many DSM diagnoses, not just PTSD (Byllesby et al, 2016; Watson, 2005; Zbozinek et al, 2012). Our findings indicate that some of these non-specific symptoms are important to the PTSD network.…”
Section: Discussionmentioning
confidence: 99%
“…Although many PTSD symptoms overlap with symptoms of other mental disorders, many disorders, particularly mood and anxiety disorders, share symptoms (Byllesby, Charak, Durham, Wang, & Elhai, 2016; Watson, 2005; Zbozinek et al, 2012). Further, there are several important questions that need to be addressed before we can presume that the non-specific symptoms can or should be eliminated.…”
mentioning
confidence: 99%
“…Emotional components of alexithymia were measured by two subscales of the Toronto Alexithymia Scale [ 30 , 31 ], namely (1) difficulties identifying one’s own feelings (DIF) (seven items) and (2) difficulties in describing one’s own feelings (DDF) (five items). As recommended by previous research, we combined these subscales into one sum scored scale [ 32 , 33 , 34 , 35 , 36 ]. Since the third subscale, externally-oriented thinking (EOT), showed low reliability in previous research and previous research revealed that alexithymia can be reliable measured among adolescents without using the EOT subscale [ 32 , 36 ] we did not measure this subscale in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…As recommended by previous research, we combined these subscales into one sum scored scale [ 32 , 33 , 34 , 35 , 36 ]. Since the third subscale, externally-oriented thinking (EOT), showed low reliability in previous research and previous research revealed that alexithymia can be reliable measured among adolescents without using the EOT subscale [ 32 , 36 ] we did not measure this subscale in the current study. To measure DIF and DDF, participants were asked to rate to what extent they agreed with statements such as “It is difficult for me to reveal my innermost feelings, even to close friends” or “It is difficult for me to find the right words for my feelings” on a five-point Likert scale, ranging from “strongly disagree” (=1) to “strongly agree” (=5).…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria for participation included children diagnosed with psychiatric disorder, intellectual disability, or a pervasive developmental disorder. A detailed description of the study can be found elsewhere ( Gao et al, 2015 , 2016 ; Fagan et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%